Memory B cells are a more reliable archive for historical antimalarial responses than plasma antibodies in no-longer exposed children. - Ndungu, F; Olotu, A; Mwacharo, J; Nyonda, M; Apfeld, J; Mramba, L; Fegan, G; Bejon, P; Marsh, K (2012)
Humans respond to foreign antigen by generating plasma Abs and memory B cells (MBCs). The Ab response then declines, sometimes to below the limit of detection. In contrast, MBCs are generally thought to be long-lived. We tested and compared Plasmodium falciparum (Pf)-specific Ab and MBC responses in two populations of children: (i) previously exposed children who had documented Pf infections several years ago, but minimal exposure since then; and (ii) persistently exposed children living in a separate but nearby endemic area. We found that although Pf-specific plasma Abs were lower in previously exposed children compared with persistently exposed children, their cognate MBCs were maintained at similar frequencies. We conclude that serological analysis by itself would greatly underestimate the true memory of Pf-specific Ab responses in previously exposed children living in areas where Pf transmission has been reduced or eliminated.